The epoxiconazole and tebuconazole fungicides impair granulosa cells functions partly through the aryl hydrocarbon receptor (AHR) signalling with contrasted effects in obese, normo-weight and polycystic ovarian syndrome (PCOS) patients - Loise Serra; Anthony Estienne; Alice Bongrani; Christelle Ramé; Giovanni Caria; Claire Froger; Claudy Jolivet; Abel Henriot; Laurence Amalric; Emilie Corbin; Fabrice Guérif; Pascal Froment; et al. (Toxicology Reports, 2024)
Polycystic ovarian syndrome (PCOS), frequently associated to obesity, is the main reproductive disorder in women in age to procreate. Some evidence suggests that pesticides can result in alterations of the female reproductive system, including polycystic ovary syndrome (PCOS). Here, we detected two fungicides, Tebuconazole (Tb) and Epoxiconazole (Epox) in the soils and waters of French area. Our hypothesis is that these two triazoles could be associated to the etiology of PCOS. We used the human KGN cell line and primary human granulosa cells (hGCs) from different group of patients: normal weight non PCOS (NW), normal weight PCOS (PCOS NW), obese (obese) and obese PCOS (PCOS obese). We exposed in vitro these cells to Tb and Epox from 0 up to 10 mM for 24 and 48 h and analysed cell viability and steroidogenesis. In hGCs NW, cell viability was reduced from 12.5 µM for Tb and 75 µM for Epox. In hGCs NW, Epox decreased progesterone (Pg) and estradiol (E2) secretions and inhibited STAR, HSD3B and CYP19A1 mRNA expressions from 25 µM and increased AHR mRNA expression from 75 µM. Tb exposure also reduced steroid secretion and STAR and CYP19A1 mRNA expressions and increased AHR mRNA expression but at cytotoxic concentrations. Silencing of AHR in KGN cells reduced inhibitory effects of Tb and Epox on steroid secretion. Tb and Epox exposure decreased more steroid secretion in hGCs from obese, PCOS NW and PCOS obese groups than in NW group. Moreover, we found a higher gene expression of AHR within these three groups. Taken together, both Epox and Tb reduced steroidogenesis in hGCs through partly AHR and Tb was more cytotoxic than Epox. These triazoles alter more strongly PCOS and/or obese hGCs suggesting that human with reproductive disorders are more sensitive to triazoles exposure.